Hubungan Mekanisme Koping Bermain Puzzle Berbasis Adaptasi dengan Aktivitas Belajar Siswa di Sekolah Dasar - Steven Aldo Marcello; Ninda Ayu Prabasari; Linda Juwita (Universitas Malahayati Lampung, 2025)
ABSTRACT Learning activities are an important principle in the teaching and learning process. In a learning process, adaptation is needed by both teachers and students (students). The researcher wanted to know the correlation between the adaptation-based puzzle game concept with student learning activities. Explanatory survey research design with a cross-sectional approach, population of 5-6 elementary school students with a total sample of 123 students using the rule of thumb. The majority of students have sufficient perception and information of playing puzzles, sufficient learning about puzzles, sufficient assessment and positive emotions in playing puzzles. Active student learning, as much as 11.4% active, 18.7% quite active, and 69.9% less active. The results of statistical tests showed that there was a significant effect between puzzles on student learning activities (p-value = 0.000). Adaptation-based puzzle games as a form of coping mechanism have a significant correlation with student learning activities, where students will adapt to a given puzzle game and can provide an adaptive response in the form of student learning activities that have active, moderately active and less active categories. Keywords: Puzzle, Learning Activity, Student ABSTRAK Aktivitas belajar merupakan prinsip yang penting dalam proses belajar mengajar. Dalam suatu proses pembelajaran, adaptasi diperlukan baik oleh guru maupun peserta didik (siswa). Peneliti ingin mengetahui hubungan konsep permainan puzzle berbasis adaptasi dengan aktivitas belajar siswa. Desain penelitian explanatory survey dengan pendekatan cross-sectional, populasi siswa kelas 5-6 SD dengan jumlah sampel sebanyak 123 siswa menggunakan rule of the thumb. Mayoritas siswa memiliki persepsi dan informasi bermain puzzle yang cukup, pembelajaran tentang puzzle yang cukup, penilaian yang cukup dan emosi yang positif dalam bermain puzzle. Keaktifan belajar siswa, sebanyak 11,4% aktif, 18,7% cukup aktif, dan 69,9% kurang aktif. Hasil uji statistik menunjukkan terdapat pengaruh yang signifikan antara puzzle terhadap aktivitas belajar siswa (p-value= 0,000). Permainan puzzle berbasis adaptasi sebagai bentuk mekanisme koping memiliki hubungan yang signifikan dengan aktivitas belajar siswa, dimana siswa akan beradaptasi dengan permainan puzzle yang diberikan dan dapat memberikan suatu respon adaptif berupa aktivitas belajar siswa yang memiliki kategori aktif, cukup aktif dan kurang aktif. Kata Kunci: Puzzle, Aktivitas Belajar, Siswa